MODERATION IN MANDAR PAPPASANG (A STUDY ON LAW ENFORCEMENT OF PAPPASANG IN MANDAR, WEST SULAWESI) - Idham Idham; Ulfiani Rahman (Al-Qalam, 2021)
Mandar as one of Indonesian ethnic groups is the majority population in West Sulawesi Province. This ethnic group has an assimilated culture with Islamic teaching values, one of which can be found in Pappasang as advices that are spoken and taught from generation to generation. This study examines Pappasang related to law enforcement. The purpose of this study is to photograph the types of Pappasang in Mandar and examine Pappasang related to law enforcement. This research is a qualitative descriptive. The data were obtained through interviews, observation, and documentation. The study showed that there were many types of Pappasang found in Mandar, such as those related to agreements, law enforcement, unity, leadership, maintaining the trust, solidarity, transparency, accountability, foresight, and so on. As for Pappasang related to law enforcement in Mandar showed many statements. One of them stated that the law is not biased towards children, family, friends or others. All are equal before the law.